Biaxially oriented polypropylene film
Patent Information
- Application Number
- JP2022533803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-03
- Filing Date
- 2021-06-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-06-14
AI Technical Summary
【0017】 本発明の二軸配向ポリプロピレン系フィルムが本来有している優れた透明性や機械的特性を損なうことなく、蒸着やコーティング、他のフィルムとのラミネート後の薄膜やコーティング層、他のフィルムとの優れた密着性を示し、滑り性、耐ブロッキング性も良好であり、加工原反に適したものであった。
Smart Images

Figure 0007631345000006 
Figure 0007631345000001 
Figure 0007631345000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polypropylene film, particularly to a biaxially oriented polypropylene film that is suitable for processing such as deposition of inorganic or organic substances, coating, lamination with other film members, and the like, because it has excellent adhesion to deposition films, coating films, and adhesives, and is less prone to wrinkling or blocking when rolled. [Background technology]
[0002] Conventionally, biaxially oriented polypropylene films have been widely used as packaging materials for various items, including food, textile products, etc., because of their excellent transparency and mechanical properties. However, problems with polypropylene films include, for example, the fact that the surface energy is small due to the non-polarity of polypropylene resins, and therefore the adhesion is insufficient in processes such as deposition of inorganic or organic substances, coating, and lamination with other film components.
[0003] In particular, when forming a thin film layer by vapor deposition or coating, there are problems not only with adhesion, but also with the protrusions caused by surface unevenness, which makes it impossible to form a thin film, resulting in poor barrier properties. On the other hand, biaxially oriented polypropylene film has poor slipperiness due to its excellent flexibility and flatness, and blocking occurs, where films stick to each other, so anti-blocking agents are generally added to form surface unevenness. As a result, the unevenness of the formed surface makes it difficult to form a thin film by vapor deposition or coating, leading to poor barrier properties.
[0004] Furthermore, since biaxially oriented polypropylene films are used for various food packaging applications, it is common to incorporate an antistatic agent into the film to prevent powders, dry foods, etc. from sticking due to static electricity, and to increase the antistatic properties by bleeding it onto the surface. However, if this antistatic agent is present on the film surface, the coating will repel the solution, resulting in defects.
[0005] Various methods have been proposed to address such problems, including a method disclosed in which branched polypropylene is mixed into propylene resin and the β-crystals of polypropylene are transformed into α-crystals to form unevenness on the film surface, thereby improving the slipperiness substantially without using an inorganic or organic antiblocking agent (see, for example, Patent Document 1, etc.).However, since only homopolypropylene with high stereoregularity is used, the surface is hard and no consideration is given to adhesion to thin films or coating layers after processing such as deposition, coating, and lamination.
[0006] On the other hand, a method has been disclosed in which antistatic agents are eliminated as much as possible, and unevenness is formed on the surface layer of the film to improve adhesion to ink or lamination with other film components (see, for example, Patent Document 2, etc.). However, higher requirements are being placed on the barrier properties and processability of thin films formed by deposition or coating. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2007 / 094072 [Patent Document 2] International Publication No. 2018 / 142983 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a biaxially oriented polypropylene film that has excellent adhesion to adhesives when laminated with vapor-deposited films, coated films, and films of other components, and has excellent film slip properties and winding quality during processing, without impairing the excellent transparency and mechanical properties that are inherent to biaxially oriented polypropylene films. [Means for solving the problem]
[0009] The present invention, which has solved the above-mentioned problems, provides a biaxially oriented polypropylene film having a base layer (A) mainly composed of a polypropylene resin, a surface layer (B) on one side of the base layer (A) and a surface layer (C) on the side of the base layer (A) opposite to the surface layer (B), wherein the surface layer (B) satisfies the following (1) to (5), and the surface layer (C) satisfies the following (6) and (7). (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 or more and 5.5 nm or less. (4) Martens hardness is 248N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness: 270N / mm 2 That's all.
[0010] In this case, it is preferable that the dynamic friction coefficient of the biaxially oriented polypropylene film is 0.6 or less.
[0011] In this case, it is preferable that the haze value of the biaxially oriented polypropylene film is 5% or less.
[0012] Furthermore, in this case, it is preferable that the maximum peak height Rp+maximum valley depth Rv of the surface layer (B) is 30 to 50 nm.
[0013] Furthermore, in this case, it is preferable that the air escape time of the biaxially oriented polypropylene film is 10 seconds or less.
[0014] Furthermore, in this case, it is preferable that the thickness of the biaxially oriented polypropylene film is 9 μm or more and 200 μm or less.
[0015] Furthermore, in this case, a laminate of the biaxially oriented polypropylene film and a non-oriented polyethylene film is preferable.
[0016] Furthermore, in this case, it is preferable that the laminate strength of the laminate is 2.0 g / 15 mm or more. Effect of the Invention
[0017] The biaxially oriented polypropylene film of the present invention exhibits excellent adhesion to thin films, coating layers, and other films after deposition, coating, and lamination with other films, without impairing the excellent transparency and mechanical properties inherent to the biaxially oriented polypropylene film of the present invention, and also has good slip properties and blocking resistance, making it suitable for processing raw rolls. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is an explanatory diagram of the installation of an apparatus and a sample film used to measure the air release time (seconds). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The biaxially oriented polypropylene film of the present invention has a base layer (A) mainly composed of a polypropylene resin, a surface layer (B) on one side of the base layer (A) and a surface layer (C) on the side of the base layer (A) opposite to the surface layer (B), wherein the surface layer (B) satisfies the following (1) to (5), and the surface layer (C) satisfies the following (6) and (7). (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 or more and 5.5 nm or less. (4) Martens hardness is 248N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness: 270N / mm 2 More than this is preferable. Here, the wetting tension of the surface layer (B) represents the surface tension (mN / m) of the mixed liquid reagent determined to wet the film surface, and is related to the wettability of printing inks and adhesives. The surface resistance of the surface layer (B) varies depending on the amount of antistatic agent present on the surface, and the smaller the amount of antistatic agent present on the surface, the higher the surface resistance.
[0020] The arithmetic mean roughness (Ra) of the surface of the surface layer (B) is determined by using a scanning probe microscope (AFM) in dynamic mode to measure in a range of 2 μm in both the X and Y directions, correcting the obtained image (tilt, line fit, noise line removal), and then determining the arithmetic mean roughness in accordance with the definition of JIS-B0601 (1994). The arithmetic mean roughness (Ra) of a 2 μm square area measured by AFM is an index that indicates the unevenness of the resin itself, excluding the relatively large peaks and valleys formed by antiblocking agents and lubricants, and is related to the adhesion with resin during processing such as deposition, coating, and lamination. A large Ra indicates that the surface has large unevenness and that the surface area of the resin that adheres during processing is large, improving adhesion. This is different from the maximum peak height Rp + maximum valley depth Rv, which will be described later.
[0021] The Martens hardness of the surface of surface layer (B) and surface layer (C) indicates the hardness of the resin when a dynamic ultra-microhardness tester is used to press a needle tip with a curvature radius of 0.1 μm or less into the surface by about 0.1 μm. A low Martens hardness of surface layer (B) indicates a soft surface, which improves the conformability of the resin surface during processing and improves adhesion. A high Martens hardness of surface layer (C) indicates a hard surface, which reduces the sinking of the convex parts formed by the anti-blocking agent and lubricant, improving slipperiness and blocking resistance while keeping the contact area small.
[0022] The central surface average roughness (SRa) of the surfaces of the surface layer (B) and the surface layer (C) was determined in accordance with the definition of arithmetic average roughness described in JIS-B0601 (1994) by measuring using a three-dimensional roughness meter with a stylus pressure of 20 mg, a measurement length of 1 mm in the X direction, a feed pitch of 2 μm in the Y direction, 99 recorded lines, a height direction magnification of 20,000 times, and a cutoff of 80 μm.
[0023] The center surface average roughness (SRa) is an index showing the surface irregularities, including the relatively large peaks and valleys formed by antiblocking agents and lubricants, and is related to the film's slipperiness, wrinkles on rolls, and blocking between films. A large SRa indicates large surface irregularities, which reduces the contact area on the surface when blocking between films or when sliding against metals, improving slipperiness and blocking resistance.
[0024] (1) Base material layer (A) The polypropylene resin constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention may be a polypropylene homopolymer containing no copolymerization component, or a polypropylene resin copolymerized with 0.5 mol% or less of ethylene and / or an α-olefin having 4 or more carbon atoms. The copolymerization component is preferably 0.3 mol% or less, more preferably 0.1 mol% or less, and a polypropylene homopolymer containing no copolymerization component is most preferred. When the copolymerization amount of ethylene and / or α-olefin having 4 or more carbon atoms is 0.5 mol % or less, the crystallinity and rigidity are unlikely to decrease, and the thermal shrinkage rate at high temperatures is unlikely to increase. These resins may be used in blend form.
[0025] This is an index of the stereoregularity of the polypropylene resin constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention. 13The mesopentad fraction ([mmmm]%) measured by C-NMR is preferably 98% or more and 99.5% or less. More preferably, it is 98.1% or more, and even more preferably, it is 98.2% or more. If the mesopentad fraction of a polypropylene-based resin is small, the elastic modulus may be low and the heat resistance may be insufficient. 99.5% is the practical upper limit.
[0026] The mass average molecular weight (Mw) of the polypropylene resin constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention is preferably 180,000 or more and 500,000 or less. If the Mw is less than 180,000, the melt viscosity is low, so the resin is not stable when cast, and film-forming properties may be poor. If the Mw is more than 500,000, the amount of components with a molecular weight of 100,000 or less becomes 35% by mass, and the heat shrinkage rate at high temperatures decreases. A more preferred lower limit of Mw is 190,000, even more preferably 200,000, and a more preferred upper limit of Mw is 320,000, even more preferably 300,000, and particularly preferably 250,000.
[0027] The number average molecular weight (Mn) of the polypropylene resin constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention is preferably 20,000 or more and 200,000 or less. If it is less than 20,000, the melt viscosity is low, so that the film-forming property may be deteriorated due to instability during casting, whereas if it exceeds 200,000, the heat shrinkage rate at high temperatures is reduced. A more preferable lower limit of Mn is 30,000, even more preferably 40,000, and particularly preferably 50,000, and a more preferable upper limit of Mn is 80,000, even more preferably 70,000, and particularly preferably 60,000.
[0028] The Mw / Mn, which is an index of molecular weight distribution, of the polypropylene resin constituting the base layer (A) is preferably 2.8 or more and 10 or less, more preferably 2.8 or more and 8 or less, even more preferably 2.8 or more and 6 or less, and particularly preferably 2.8 or more and 5.4 or less. The lower limit is preferably 3 or more, and more preferably 3.3 or more. The molecular weight distribution of the polypropylene-based resin can be adjusted by polymerizing components having different molecular weights in a series of plants in multiple stages, blending components having different molecular weights offline in a kneader, blending catalysts having different performances and polymerizing the blended components, or using a catalyst that can realize a desired molecular weight distribution.
[0029] When the polypropylene resin constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention has an Mw / Mn ratio in the range of 2.8 to 5.4, it is preferable that the melt flow rate (MFR; 230°C, 2.16 kgf) is 2 g / 10 min or more and 20 g / 10 min or less. The lower limit of the MFR of the polypropylene resin of the base layer (A) is more preferably 3 g / 10 min, further preferably 4 g / 10 min, and particularly preferably 5 g / 10 min. The upper limit of the MFR of the polypropylene resin of the base layer (A) is more preferably 15 g / 10 min, and further preferably 12 g / 10 min. When the Mw / Mn and MFR of the polypropylene resin constituting the base layer (A) are within this range, the heat shrinkage rate at high temperatures can be kept small, and the adhesion to the cooling roll is good, resulting in excellent film formability.
[0030] (2) Surface layer (B) The arithmetic mean roughness (Ra) of the surface of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is preferably 3.0 to 5.5 nm. If the arithmetic mean roughness (Ra) is less than 3.0 nm, the surface area of the surface layer (B) is small, and there is a problem of reduced adhesion during processing such as deposition, coating, lamination, etc. If the arithmetic mean roughness (Ra) is more than 5.5 nm, the surface unevenness is large, and holes occur during deposition or coating, resulting in poor barrier properties, etc. The arithmetic mean roughness (Ra) of the surface of the surface layer (B) is more preferably 3.2 nm or more, further preferably 3.3 nm or more, particularly preferably 3.5 nm or more, and most preferably 4.0 nm or more. In order to make the arithmetic mean roughness (Ra) of the surface of the surface layer (B) 3.0 to 5.5 nm, it is preferable to use a mixture of two or more polypropylene resins with different melt flow rates (MFR) as the polypropylene resin composition forming the surface layer (B). In this case, the difference in MFR is preferably 3 g / 10 min or more, more preferably 3.5 g / 10 min or more. As mentioned above, it is assumed that if the difference in melt flow rate (MFR) between two or more polypropylene resins in a polypropylene resin mixture is different, the crystallization speed and degree of crystallization of each polypropylene resin will be different, and therefore surface irregularities are likely to occur. However, care must be taken because if the crystallization degree of the polypropylene resin is high or the cooling rate of the unstretched sheet during film production is slow, the surface irregularities caused by spherulites will become large, and if the stretching temperature during longitudinal or transverse stretching is too high and the surface irregularities become large, the arithmetic average roughness (Ra) may exceed 5.5 nm. As polypropylene resins with a smaller MFR, polypropylenes copolymerized with ethylene and / or α-olefins having 4 or more carbon atoms can be used. Examples of α-olefins having 4 or more carbon atoms include 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. In addition, polar maleic acid and the like can be used as other copolymerization components. The total amount of ethylene and / or α-olefins having 4 or more carbon atoms and other copolymerization components is preferably 8.0 mol% or less. If copolymerized in excess of 8.0 mol%, the film may whiten and have a poor appearance, or may become sticky, making film formation difficult. These resins may be used in combination of two or more kinds. When blended, each resin may be copolymerized in an amount exceeding 8.0 mol%, but the blend preferably contains 8.0 mol% or less of monomers other than propylene in monomer units. As the polypropylene resin having a larger MFR, the above-mentioned copolymer polypropylene can be used, or a homopolypropylene resin can be used. The mixing ratio of the polypropylene resin with a smaller MFR to the polypropylene resin with a larger MFR is preferably in the range of 1 wt% / 99 wt%-49 wt% / 51 wt%, more preferably in the range of 1 wt% / 99 wt%-30 wt% / 70 wt%, and even more preferably in the range of 1 wt% / 99 wt%-10 wt% / 90 wt%.
[0031] In addition, the polypropylene resin composition constituting the surface layer (B) of the biaxially oriented polypropylene film of the present invention preferably has an MFR of 1.0 g / 10 min or more and 10.0 g / 10 min or less. The lower limit of the MFR of the polypropylene resin composition of the surface layer (B) is more preferably 2.0 g / 10 min, even more preferably 3.0 g / 10 min, and particularly preferably 4.0 g / 10 min. The upper limit of the MFR of the polypropylene resin composition constituting the surface layer (B) is more preferably 9.0 g / 10 min, even more preferably 8.0 g / 10 min, and particularly preferably 5.5 g / 10 min. Within this range, the film formability is good and the appearance is excellent. If the MFR of the polypropylene resin composition constituting the surface layer (B) is smaller than 1.0 g / 10 min, when the MFR of the polypropylene resin composition constituting the base layer (A) is large, the viscosity difference between the base layer (A) and the surface layer (B) becomes large, so that unevenness (unevenness of the original roll) is likely to occur during film formation. If the MFR of the polypropylene-based resin composition constituting the surface layer (B) exceeds 10 g / 10 min, the adhesion to the cooling roll will be poor, air will be entrapped, the smoothness will be poor, and there is a risk that many defects will occur due to this.
[0032] In addition, the surface of the surface layer (B) of the biaxially oriented polypropylene film preferably has a center surface average roughness (SRa) of 0.010 μm or more and 0.026 μm or less, as measured by a three-dimensional roughness meter. The center surface average roughness (SRa) of the surface layer (B) is more preferably 0.012 μm or more and 0.025 μm or less, more preferably 0.015 μm or more and 0.025 μm or less, and particularly preferably 0.020 μm or more and 0.024 μm or less. If the center surface average roughness (SRa) of the surface layer (B) is less than 0.010 μm, the surface unevenness is small, and the slipperiness of the film, the air release time between the films, and the blocking resistance are deteriorated. If the center plane average roughness (SRa) of the surface of the surface layer (B) exceeds 0.026 μm, the antiblocking agent may penetrate the thin film layer when applying a thin film layer such as aluminum deposition or coating, or a thin film may not be formed on the side of the convex part, resulting in reduced barrier properties and poor adhesion. There are several methods for keeping the center plane average roughness (SRa) of the surface of the surface layer (B) within the specified range, but it can be adjusted by the average particle size and amount of the antiblocking agent added. The antiblocking agent can be appropriately selected from inorganic particles such as silica, calcium carbonate, kaolin, and zeolite, and organic particles such as acrylic, polymethacrylic, and polystyrene. Among these, it is particularly preferable to use silica or polymethacrylic particles. The preferred average particle size of the antiblocking agent is 1.0 μm or more and 3.0 μm or less, and more preferably 1.0 μm or more and 2.7 μm or less. The average particle size is measured by taking a photograph with a scanning electron microscope, measuring the Feret's diameter in the horizontal direction using an image analyzer, and expressing the average value. There are no particular limitations on the amount of anti-blocking agent added, so long as the amount added to the surface layer (B) and surface layer (C) is adjusted so that the haze, dynamic friction coefficient, center surface average roughness (SRa), and air release time are within the specified ranges.
[0033] The surface resistance of the surface of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is preferably 14 Log Ω or more. If the surface resistance is 14 Log Ω or more, the adhesion to the deposition film, coating film, and adhesive is improved. The surface resistance is more preferably 14.5 Log Ω or more, and even more preferably 15 Log Ω or more. If the surface resistance is less than 14 Log Ω, not only will the adhesion decrease, but the antistatic agent that has bled to the surface layer (B) will repel the coat, resulting in poor coating. In order to achieve a surface resistance of 14 Log Ω or more, it is recommended to avoid using additives such as antistatic agents and antifogging agents as much as possible. In addition, caution is required because additives contained in the base layer (A) may bleed onto the surface of the surface layer (B).
[0034] The surface wet tension of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is preferably 38 mN / m or more. If the wet tension is 38 mN / m or more, the adhesion to the adhesive used for laminating the vapor deposition film, coating film, and other member film is improved. In order to make the wet tension 38 mN / m or more, additives such as antistatic agents and surfactants are usually used, but these methods have the effect of lowering the surface resistance value, so it is preferable to carry out physicochemical surface treatments such as corona treatment and flame treatment. For example, in the corona treatment, it is preferable to use a preheat roll and a treatment roll and perform discharge in the air.
[0035] The Martens hardness of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is 248 N / mm 2 It is preferable that the resistance is less than or equal to 245 N / mm 2 or less, and more preferably 240 N / mm 2 or less, and particularly preferably 235 N / mm 2 or less, most preferably 230N / mm 2 The following is the result. Martens hardness is 248N / mm 2 If the hardness exceeds 248N / mm, the surface becomes hard, the conformability of the resin surface during processing becomes poor, and the adhesive strength decreases. 2To lower the Martens hardness, ethylene and / or an α-olefin having 4 or more carbon atoms, or other copolymerization components can be added. In addition, the Martens hardness can also be lowered by lowering the stretch ratio of the film and decreasing the orientation of the molecular chains. The surface layer (B) of the biaxially oriented polypropylene film of the present invention has a Martens hardness of 200 N / mm 2 It is preferable that the resistance is equal to or higher than 210 N / mm 2 That's all.
[0036] The maximum peak height Rp + maximum valley depth Rv of the surface of the surface layer (B) of the biaxially oriented polypropylene film of the present invention measured by AFM is preferably 30 to 50 nm. The lower limit of the maximum peak height Rp + maximum valley depth Rv of the surface of the surface layer (B) is more preferably 32 nm, even more preferably 35 nm, and particularly preferably 38 nm. The upper limit of the maximum peak height Rp + maximum valley depth Rv of the surface of the surface layer (B) is more preferably 48 nm, and particularly preferably 45 nm. The maximum peak height Rp and maximum valley depth Rv are not due to the antiblocking agent, but due to the unevenness of the resin itself. When the maximum peak height Rp + maximum valley depth Rv is 30 nm or more, air escape due to contact with the surface layer (C) in a rolled state and blocking resistance are improved. In addition, the surface area of the surface layer (B) is increased, improving adhesion to the vapor deposition layer and coating layer. However, because air escape and blocking resistance are also closely related to the central surface roughness (SRa) measured by a three-dimensional roughness gauge (described later), even if the maximum peak height Rp and maximum valley depth Rv are less than 30 nm, it is possible that air escape and blocking resistance will be good if the central surface roughness (SRa) of the surface layers (B) and (C) is large. If the maximum peak height Rp + maximum valley depth Rv is 50 nm or less, the surface unevenness will not be too large, evaporation layer or coating layer will not easily come off, and barrier properties will be improved.
[0037] (3) Surface layer (C) The surface layer (C) of the biaxially oriented polypropylene film of the present invention preferably has a center surface average roughness (SRa) of 0.020 μm or more as measured by a three-dimensional roughness meter. The center surface average roughness (SRa) of the surface layer (C) is more preferably 0.022 μm or more, even more preferably 0.025 μm, and particularly preferably 0.028 μm. If the center plane average roughness (SRa) of the surface layer (C) is less than 0.020 μm, the surface unevenness will be small, and the film's slipperiness, air release time between films, and blocking resistance will be poor. There are several methods for keeping the center plane average roughness (SRa) of the surface layer (C) within the specified range, and it can be adjusted by the average particle size and amount of the antiblocking agent added. The surface layer (C) of the biaxially oriented polypropylene film of the present invention preferably has a center surface average roughness (SRa) of 0.040 μm or less as measured by a three-dimensional roughness meter.
[0038] In addition, the Martens hardness of the surface layer (C) of the biaxially oriented polypropylene film is 270N / mm 2 More preferably, it is 275N / mm 2 More preferably, 280N / mm 2 More preferably, 285N / mm 2 That's all. Martens hardness is 270N / mm 2 If the hardness is less than 270N / mm, the surface is soft and the anti-blocking agent sinks into the resin, resulting in poor slipperiness and anti-blocking properties. 2 To achieve the Martens hardness or higher, it is preferable to use polypropylene copolymerized with 0.5 mol% or less of ethylene and / or an α-olefin having 4 or more carbon atoms, but 0.1 mol% or less is more preferable, and completely homopolypropylene containing no copolymerization component is most preferable. It is also possible to increase the Martens hardness by setting the mesopentad fraction ([mmmm]%) of the constituent polypropylene to 98% or more and increasing the crystallinity. The Martens hardness of the surface layer (C) of the biaxially oriented polypropylene film is 350N / mm 2 It is preferable that:
[0039] The polypropylene resin used in the present invention is obtained by polymerizing the raw material propylene using a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst. Among them, it is preferable to use a Ziegler-Natta catalyst in order to eliminate heterogeneous bonds, and to use a catalyst capable of polymerization with high stereoregularity. As a method for polymerizing the raw material propylene, a known method may be adopted, and examples thereof include a method of polymerizing in an inert solvent such as hexane, heptane, toluene, or xylene, a method of polymerizing in a liquid monomer, a method of adding a catalyst to a gaseous monomer and polymerizing in a gas phase state, or a method of polymerizing by combining these methods.
[0040] The base layer (A) and / or the surface layer (B) and / or the surface layer (C) of the biaxially oriented polypropylene film of the present invention may contain additives and other resins. Examples of additives include antioxidants, ultraviolet absorbers, nucleating agents, adhesives, antifogging agents, flame retardants, inorganic or organic fillers, etc. Examples of other resins include polypropylene resins other than the polypropylene resin used in the present invention, random copolymers which are copolymers of propylene and ethylene and / or α-olefins having 4 or more carbon atoms, and various elastomers. These may be sequentially polymerized using a multi-stage reactor, blended with polypropylene resin using a Henschel mixer, master pellets prepared in advance using a melt kneader may be diluted with polypropylene to a predetermined concentration, or the entire amount may be melt kneaded in advance before use.
[0041] (3) Biaxially oriented polypropylene film The biaxially oriented polypropylene film of the present invention may have a three-layer structure of surface layer (B) / base layer (A) / surface layer (C), a four-layer structure of surface layer (B) / intermediate layer (D) / base layer (A) / intermediate layer (D) / surface layer (C), or a surface layer (B) / base layer (A) / intermediate layer (D) / surface layer (C), or a multilayer structure having more than one layer.
[0042] The overall thickness of the biaxially oriented polypropylene film of the present invention is preferably 9 μm or more and 200 μm or less, more preferably 10 μm or more and 150 μm or less, even more preferably 12 μm or more and 100 μm or less, and particularly preferably 15 μm or more and 80 μm or less.
[0043] The ratio of the thickness of the surface layer (B) to the thickness of the base layer (A) in the biaxially oriented polypropylene film of the present invention, i.e., the thickness of all surface layers (B) / the thickness of all base layers (A), is preferably 0.01 to 0.50, more preferably 0.02 to 0.40, even more preferably 0.03 to 0.30, and particularly preferably 0.04 to 0.20. If the thickness of all surface layers (B) / the thickness of all base layers (A) exceeds 0.50, the shrinkage rate tends to increase.
[0044] In addition, the ratio of the thickness of the surface layer (C) to the thickness of the base layer (A) in the biaxially oriented polypropylene film is preferably 0.01 to 0.50, more preferably 0.02 to 0.40, even more preferably 0.03 to 0.30, and particularly preferably 0.04 to 0.20. If the ratio of the thickness of the surface layer (C) to the thickness of the base layer (A) exceeds 0.50, the haze increases and the transparency deteriorates depending on the amount of antiblocking agent added.
[0045] In addition, the thickness of the base layer (A), or the total thickness of the base layer (A) and the intermediate layer (D), relative to the thickness of the entire film is preferably 50% or more and 99% or less, more preferably 60% or more and 97% or less, particularly preferably 70% or more and 90% or less, and most preferably 80% or more and 92% or less.
[0046] The haze of the biaxially oriented polypropylene film of the present invention is preferably 5% or less, more preferably 0.2% or more and 5.0% or less, even more preferably 0.3% or more and 4.5%, and particularly preferably 0.4% or more and 4.0%. When it is within the above range, it may be easy to use in applications where transparency is required. For example, the haze tends to deteriorate when the stretching temperature or heat setting temperature is too high, the cooling roll temperature is high and the cooling rate of the unstretched (raw) sheet is slow, or there is too much low molecular weight component, and it can be adjusted to the above range. The method for measuring the haze will be described later.
[0047] The longitudinal tensile modulus of the biaxially oriented polypropylene film of the present invention is preferably 1.8 to 4.0 GPa, more preferably 2.0 to 3.7 GPa, even more preferably 2.1 to 3.5 GPa, and particularly preferably 2.2 to 3.4 GPa. The tensile modulus in the transverse direction of the biaxially oriented polypropylene film of the present invention is preferably 3.8 GPa or more and 8.0 GPa or more, more preferably 4.0 GPa or more and 7.5 GPa or less, even more preferably 4.1 GPa or more and 7.0 GPa or less, and particularly preferably 4.2 GPa or more and 6.5 GPa or less. If the tensile modulus is within the above range, the film will be strong and can be used even with a small film thickness, making it possible to reduce the amount of film used. The method for measuring the tensile modulus will be described later.
[0048] In the biaxially oriented polypropylene film of the present invention, the longitudinal heat shrinkage at 150°C is preferably 0.2 to 15.0%, more preferably 0.3 to 13.0%, even more preferably 0.5 to 11.0%, and particularly preferably 0.5 to 9.0%. If the heat shrinkage is within the above range, the film can be said to have excellent heat resistance and can be used in applications where it may be exposed to high temperatures. The 150°C heat shrinkage can be reduced to about 1.5% by, for example, increasing the amount of low molecular weight components or adjusting the stretching conditions and heat setting conditions, but to reduce it below that, it is preferable to perform offline annealing treatment, etc. In the biaxially oriented polypropylene film of the present invention, the transverse heat shrinkage at 150°C is preferably 0.5 to 30.0%, more preferably 0.5 to 25.0%, even more preferably 0.5 to 20.0%, and particularly preferably 0.5 to 18.0%. If the heat shrinkage is within the above range, the film can be said to have excellent heat resistance and can be used in applications where it may be exposed to high temperatures. The 150°C heat shrinkage can be reduced to about 1.5% by, for example, increasing the amount of low molecular weight components or adjusting the stretching conditions and heat setting conditions, but to reduce it below that, it is preferable to perform an offline annealing treatment. The method for measuring the heat shrinkage will be described later.
[0049] The dynamic friction coefficient of the biaxially oriented polypropylene film of the present invention is preferably 0.6 or less, more preferably 0.55 or less, and particularly preferably 0.50 or less. If the dynamic friction coefficient is 0.6 or less, the film can be smoothly unwound from the roll film, and printing processing is easy. The dynamic friction coefficient may be 0.1 or more. The method for measuring the dynamic friction coefficient will be described later.
[0050] The air escape time of the biaxially oriented polypropylene film of the present invention is preferably 10 seconds or less, more preferably 8 seconds or less, even more preferably 5 seconds or less, and particularly preferably 3 seconds or less. If the air escape time exceeds 10 seconds, the air escapes slowly when rolled, and wrinkles are likely to occur. The air escape time may be 1 second or more. The method for measuring the air escape time will be described later. When the biaxially oriented polypropylene film of the present invention is wound into a film roll having a width of 300 mm and a length of 800 m or more, it is suitable for transportation and for deposition processing, coating processing, and bag making processing. When the biaxially oriented polypropylene film of the invention is wound up to a width of 500 mm and a length of 1000 m, and the wrinkles on the surface of the roll are visually evaluated according to the following criteria, there are weak wrinkles, but it is preferable that the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film, and it is even more preferable that there are no wrinkles.
[0051] When it is desired to improve the gas barrier properties or design properties of the biaxially oriented polypropylene film of the invention, it is preferable to provide a layer, particularly a thin layer, made of aluminum, polyvinylidene chloride, nylon, ethylene-vinyl alcohol copolymer, or polyvinyl alcohol. It is preferable that the aluminum thin film layer is only partially peeled off from the aluminum thin film provided on the surface of the biaxially oriented polypropylene film of the invention, and it is more preferable that the aluminum thin film layer is not partially peeled off. Furthermore, when a coating layer is provided on the surface of the biaxially oriented polypropylene film of the invention, it is preferable that there is only slight cissing of the coating layer, and it is more preferable that there is no cissing of the coating layer. It is also preferred to process the biaxially oriented polypropylene film of the present invention or a film having a thin film layer thereon into a packaging bag using a laminate of an unstretched film, a uniaxially oriented film, or a biaxially oriented film made of low density polyethylene, linear low density polyethylene, an ethylene-vinyl acetate copolymer, polypropylene, or polyester. The laminate strength of the laminate of the biaxially oriented polypropylene film and the unstretched polyethylene film of the present invention is preferably 2.0 N / 15 mm or more, more preferably 2.3 N / mm or more, even more preferably 2.5 N / mm or more, and particularly preferably 2.8 N / mm or more. The laminate strength may be 5 N / mm or less. The method for measuring the laminate strength will be described later.
[0052] (4) Manufacturing method The biaxially oriented polypropylene film of the present invention can be obtained by melt-extruding the polypropylene resin composition constituting the base layer (A), the polypropylene resin composition constituting the surface layer (B), and the polypropylene resin composition of the surface layer (C) using separate extruders, co-extruding them from a die, and cooling them with a cooling roll to form an unstretched sheet, stretching the unstretched sheet in the machine direction (MD) and the transverse direction (TD), and then heat-setting the sheet. It is preferable to extrude the surface layer (B) so that the surface layer (B) is in contact with the cooling roll. If the surface layer (B) is on the opposite side to the surface that is in contact with the cooling roll, the polypropylene resin is slowly cooled, the crystallization degree is increased, and the arithmetic average roughness (Ra) of the surface of the surface layer (B) may become too large due to surface unevenness caused by spherulites. The melt extrusion temperature is preferably about 200 to 280°C. In order to obtain a laminated film with good appearance without disturbing the layers within this temperature range, it is preferable that the viscosity difference (MFR difference) between the polypropylene resin composition constituting the base layer (A) and the polypropylene resin composition constituting the surface layer (B) is 6.0 g / 10 min or less. If the viscosity difference is more than 6 g / 10 min, the layers are likely to be disturbed and the appearance is likely to be poor. It is more preferably 5.5 g / 10 min or less, and even more preferably 5.0 g / 10 min or less.
[0053] The surface temperature of the cooling roll is preferably 25° C. or more and 35° C. or less, and more preferably 27° C. or more and 33° C. or less. If the cooling roll temperature exceeds 35° C., the degree of crystallization of the polypropylene-based resin increases, and the arithmetic mean roughness (Ra) of the surface of the surface layer (B) may become too large due to surface irregularities of the formed spherulites.
[0054] The lower limit of the stretching ratio in the machine direction (MD) is preferably 3 times, more preferably 3.5 times. If it is less than the above, the film thickness may become uneven. The upper limit of the stretching ratio in the MD is preferably 8 times, more preferably 7 times. If it exceeds the above, the subsequent TD stretching may become difficult. The lower limit of the MD stretching temperature is preferably 120 ° C, more preferably 125 ° C, and even more preferably 130 ° C. If it is less than the above, the mechanical load may become large, the thickness unevenness may become large, and the surface of the film may become rough. The upper limit of the MD stretching temperature is preferably 160 ° C, more preferably 155 ° C, and even more preferably 150 ° C. A higher temperature is preferable for reducing the heat shrinkage rate, but it may adhere to the roll, making it impossible to stretch, or the surface may become rough.
[0055] The lower limit of the stretching ratio in the transverse direction (TD) is preferably 4 times, more preferably 5 times, and even more preferably 6 times. If it is less than the above, thickness unevenness may occur. The upper limit of the TD stretching ratio is preferably 20 times, more preferably 17 times, even more preferably 15 times, and particularly preferably 12 times. If it exceeds the above, the heat shrinkage rate may increase or the film may break during stretching. The preheating temperature in TD stretching is preferably set to be 5 to 15°C higher than the stretching temperature in order to quickly raise the film temperature to the vicinity of the stretching temperature. The lower limit of the TD stretching temperature is preferably 150°C, more preferably 155°C, even more preferably 158°C, and especially preferably 160°C. If it is less than the above, the film may break due to insufficient softening, or the heat shrinkage rate may increase. The upper limit of the TD stretching temperature is preferably 170°C, more preferably 168°C, and even more preferably 165°C. To reduce the heat shrinkage rate, a higher temperature is preferable, but if the temperature exceeds the above range, the low molecular weight components will melt and recrystallize, causing not only a decrease in orientation but also surface roughness and whitening of the film.
[0056] The stretched film is heat set. The lower limit of the heat setting temperature is preferably 163°C, more preferably 165°C. If the temperature is lower than the above, the heat shrinkage rate may be high. In addition, a long period of treatment may be required to reduce the heat shrinkage rate, which may result in poor productivity. The upper limit of the heat setting temperature is preferably 176°C, more preferably 175°C. If the temperature exceeds the above range, low molecular weight components may melt and recrystallize, causing surface roughness and whitening of the film.
[0057] It is preferable to relax the film during heat setting. The lower limit of the relaxation rate is preferably 2%, more preferably 3%. If it is less than the above, the thermal shrinkage rate may be high. The upper limit of the relaxation rate is preferably 10%, more preferably 8%. If it exceeds the above, the thickness unevenness may become large.
[0058] Furthermore, in order to reduce the thermal shrinkage rate, the film produced by the above process may be wound into a roll and then annealed offline.
[0059] The biaxially oriented polypropylene film thus obtained can be subjected to corona discharge, plasma treatment, flame treatment, etc., as required, and then wound up with a winder to obtain the biaxially oriented polypropylene film roll of the present invention. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples. However, the following examples do not limit the present invention, and any modifications and variations that do not depart from the spirit of the present invention are included in the present invention.
[0061] (Measurement method) The raw materials used in the examples and comparative examples and the methods for measuring the physical properties of the obtained films are as follows.
[0062] 1) Mesopentad fraction ([mmmm] unit: %) The mesopentad fraction is measured by 13The mesopentad fraction was calculated according to the method described in "Zambelli et al., Macromolecules, Vol. 6, p. 925 (1973)". 13 C-NMR measurements were performed using a BRUKER AVANCE500 at 110°C by dissolving 200 mg of a sample in a mixed solution of o-dichlorobenzene and deuterated benzene at a volume ratio of 8:2 at 135°C.
[0063] 2) Melt flow rate ([MFR]g / 10 min) The measurements were performed in accordance with JIS K7210 at a temperature of 230°C and a load of 2.16 kgf. In the case of raw resin, the pellets (powder) were weighed out and used in the required amount. In the case of film, the required amount was cut out and then cut into samples of approximately 5 mm square.
[0064] 3) Molecular weight and molecular weight distribution The molecular weight and molecular weight distribution of the raw material resin and the film were determined by gel permeation chromatography (GPC) using monodisperse polystyrene as a standard. The measurement conditions such as the column and solvent used in the GPC measurement are as follows: Solvent: 1,2,4-trichlorobenzene Column: TSKgel GMHHR-H(20)HT x 3 Flow rate: 1.0ml / min Detector: RI Measurement temperature: 140℃
[0065] The number average molecular weight (Mn), mass average molecular weight (Mw), and molecular weight distribution (Mw / Mn) are calculated by the molecular weight (M i ) number of molecules (N i ) is defined by the following formula: Number average molecular weight: Mn=Σ(N i M i ) / ΣN i Mass average molecular weight: Mw=Σ(N i M i 2 ) / Σ(Ni M i ) Molecular weight distribution: Mw / Mn When the baseline was unclear, the baseline was set in the range up to the lowest position of the high molecular weight side tail of the elution peak on the high molecular weight side closest to the elution peak of the standard substance.
[0066] 4) Melting peak temperature (℃), melting peak area (J / g) Using a differential scanning calorimeter (DSC) manufactured by SII, measurements were performed with a sample weight of 10 mg and a heating rate of 20° C. / min. The melting endothermic peak temperature and melting peak area were determined from the DSC curve.
[0067] 5) Thickness (μm) The thickness of each of the base layer (A) and surface layer (B) was measured by cutting a cross section of a biaxially oriented laminated polypropylene film solidified with a modified urethane resin using a microtome and observing it with a differential interference microscope.
[0068] 6) Haze (%) Measurement was performed at 23° C. in accordance with JIS K 7105. Measurement was performed using a haze meter (300A, manufactured by Nippon Denshoku Industries Co., Ltd.) The measurement was performed twice, and the average value was calculated.
[0069] 7) Tensile modulus (GPa) Measurements were performed according to JIS K 7127. A sample with a width of 10 mm and a length of 180 mm was cut out using a razor in the longitudinal and transverse directions of the film. After leaving the film for 12 hours in an atmosphere of 23°C and 65% RH, measurements were performed under conditions of 23°C, 65% RH, chuck distance of 100 mm, and pulling speed of 200 mm / min, and the average value of five measurement results was used. The measurement device used was an autograph AG5000A manufactured by Shimadzu Corporation.
[0070] 8) Heat shrinkage rate (%) The measurement was performed according to the following method in accordance with JIS Z1712. The film was cut to a width of 20 mm and a length of 200 mm in each of the MD and TD directions, and was hung in a hot air oven at 150°C and heated for 5 minutes. The length before and after heating was measured, and the ratio (%) of the length before heating minus the length after heating to the length before heating was calculated to determine the thermal shrinkage rate.
[0071] 9) Wetting tension (mN / m) In accordance with K 6768:1999, the film was aged at 23°C and 50% relative humidity for 24 hours, and then the corona-treated surface of the film was measured using the following procedure. Step 1) The measurements shall be carried out in a standard laboratory atmosphere (see JIS K 7100) with a temperature of 23°C and a relative humidity of 50%. Step 2) The test specimen is placed on the substrate of the hand coater (4.1), a few drops of the test mixture are placed on the specimen, and immediately spread by pulling the wire bar. If a cotton swab or brush is used to spread the test mixture, the liquid should be spread to at least 6 cm 2 Spread the liquid quickly over the above area. The amount of liquid should be enough to form a thin layer without creating any puddles. The wetting tension is judged by observing the liquid film of the test mixture in a bright place and the state of the liquid film after 3 seconds. If the liquid film does not break and the state at the time of application is maintained for 3 seconds or more, it is considered to be wet. If the wetness is maintained for 3 seconds or more, proceed to the mixed liquid with the next higher surface tension, and conversely, if the liquid film breaks in 3 seconds or less, proceed to the mixed liquid with the next lower surface tension. Repeat this process to select the mixture that can accurately wet the surface of the test piece within 3 seconds. Step 3) Use a new swab for each test. Brushes or wire bars should be cleaned with methanol and dried after each use, as residual liquid will change composition and surface tension upon evaporation. Step 4) The procedure is repeated at least three times to select the mixture that can wet the surface of the test piece in 3 seconds, and the surface tension of the mixture thus selected is reported as the wetting tension of the film.
[0072] 10) Surface resistance value (LogΩ) According to JIS K6911, the film was aged at 23° C. for 24 hours, and then the surface layer (B) of the film was measured.
[0073] 11) Coefficient of kinetic friction In accordance with JIS K7125, the surface layers (B) of two films were placed together and the measurement was carried out at 23°C.
[0074] 12) Air release time (seconds) As shown in Figure 1, a biaxially oriented polypropylene film is placed on base 1 as film 4 with the surface layer (B) facing up. Next, film holder 2 is placed on top of film 4 and fixed in place to apply tension to film 4. Next, a biaxially oriented polypropylene film is placed on top of film holder 2 as film 5 with the surface layer (C) facing down. Next, film holder 8 is placed on top of film 5, and screws 3 are used to fix film holders 8, 2 and base 1 together. Next, cavity 2a in film holder 2 is connected to vacuum pump 6 via small hole 2c in film holder 2 and pipe 7. When vacuum pump 6 is driven, film 5 is sucked into cavity 2a and tension is applied to it. At the same time, the pressure in the overlapping surfaces of films 4 and 5 is reduced via small hole 2d provided circumferentially in film holder 2, and films 4 and 5 begin to adhere to each other from the outer periphery at their overlapping surfaces. The state of adhesion can be easily confirmed by observing the interference fringes from above the overlapping surfaces. Then, the time (seconds) from when interference fringes appear on the outer periphery of the overlapping surfaces of films 4 and 5 until they spread to the front of the overlapping surfaces and stop moving is measured, and this time (seconds) is the air release time. The measurement is repeated five times by replacing the two films, and the average value is used. In other words, the shorter the time (seconds), the better the film winding characteristics.
[0075] 13) Martens hardness HMs (N / mm 2 ) The obtained film was cut into approximately 2 cm squares, and the surface opposite to the measurement surface was fixed with an adhesive on a glass plate with a thickness of approximately 1 mm, and then the plate was left in an atmosphere of 23°C and 50% RH for 12 hours to condition the humidity. This sample was measured using a dynamic ultra-microhardness tester (Shimadzu Corporation's "DUH-211") under the following measurement conditions according to the method of ISO14577-1 (2002). The measurement was performed 10 times by changing the position of the film, and the average value of 8 points excluding the maximum and minimum was calculated.
[0076] <Measurement conditions> (setting) Measurement environment: Temperature 23°C, relative humidity 50% Test mode: Load-unload test Indenter used: Triangular pyramid indenter (made of diamond) with 115 degree inter-edge angle Indentation modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Cf-Ap,As correction: Yes (conditions) Test force: 0.10mN ·Load speed: 0.0050mN / sec ·Load holding time: 5sec ·Unloading holding time: 0sec The Martens hardness was calculated from the slope (m) of the test force vs. indentation depth curve, where the depth between 50% F and 90% F (F = 0.10 mN) of the test force is proportional to the square root of the test force, using the following formula (1). Martens hardness HMs=1 / (26.43×m 2 ) · · · · (1)
[0077] 14) Center surface average roughness ([SRa]μm) The center surface average roughness (SRa) of the obtained film was measured using a three-dimensional roughness meter (manufactured by Kosaka Laboratory, model number ET-30HK) with a stylus pressure of 20 mg, a measurement length in the X direction of 1 mm, a feed speed of 100 μm / sec, a feed pitch in the Y direction of 2 μm, 99 recorded lines, a height direction magnification of 20,000 times, and a cutoff of 80 μm, and calculated in accordance with the definition of arithmetic average roughness described in JIS-B0601 (1994). The arithmetic mean roughness (SRa) was evaluated by averaging three trials each.
[0078] 15)Arithmetic mean roughness ([Ra] nm), maximum peak height ([Rp] nm), maximum valley depth ([Rv] nm) The arithmetic mean roughness (Ra), maximum peak height (Rp), and maximum valley depth (Rv) of the obtained film was measured using a scanning probe microscope (Shimadzu Corporation, "SPM-9700") in dynamic mode, with measurement lengths in both the X and Y directions in a range of 2 μm, and the obtained images were corrected (tilt, line fit, noise line removal), and then calculated according to the definition of arithmetic mean roughness described in JIS-B0601 (1994).
[0079] 16) Laminate strength (N / 15mm) The laminate strength was measured by the following procedure. Step 1) Preparation of a laminate of biaxially oriented polypropylene film and non-oriented polyethylene film The lamination was carried out using a continuous dry laminating machine as follows. The adhesive was applied to the surface layer (B) of the biaxially oriented polypropylene film obtained in the Examples and Comparative Examples in an amount of 2.8 g / m2 when dried. 2After gravure coating so that the film was coated, it was introduced into a drying zone and dried at 80°C for 5 seconds. Then, it was laminated with a sealant film between rolls installed downstream (roll pressure: 0.2 MPa, roll temperature: 50°C). The obtained laminate film was aged at 40°C for 3 days in a rolled state. The adhesive used was a urethane adhesive obtained by mixing 28.9% by mass of a base agent (TM569, manufactured by Toyo Morton), 4.00% by mass of a hardener (CAT10L, manufactured by Toyo Morton), and 67.1% by mass of ethyl acetate, and the sealant film used was a non-oriented polyethylene film manufactured by Toyobo Co., Ltd. (Rix (registered trademark) L4102, thickness 40 μm). Step 2) Measuring laminate strength The laminate film obtained above was cut into a rectangular shape (200 mm long, 15 mm wide) with the long side in the machine direction of the biaxially oriented polypropylene film, and the peel strength (N / 15 mm) was measured using a tensile tester (Tensilon, manufactured by Orientec Co., Ltd.) when T-shaped peeling was performed at a tensile speed of 200 mm / min in an environment of 23° C. The measurement was performed three times, and the average value was taken as the laminate strength.
[0080] 17) Film roll wrinkle evaluation The biaxially oriented polypropylene film thus produced was wound up to a width of 500 mm and a length of 1000 m, and the wrinkles on the surface of the roll were visually evaluated according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film.
[0081] 18) Court suitability evaluation Butanediol-vinyl alcohol copolymer (Nichigo-G-Polymer OKS-8049, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) was dissolved in a 15% aqueous solution of isopropyl alcohol to prepare a coating solution with a solid content concentration of 5%. The prepared coating solution was dropped onto the surface layer (B) of the film and dried with a Mayer bar #3 to obtain a coating solution of 0.2 g / m. 2The coating was performed so that the coating amount was 100%. The solution was then thoroughly evaporated using a dryer, and the coating layer was visually evaluated for repelling. The evaluation results were judged as 40% or 0%. ◎: No repelling of the coating layer 〇: 90% of the coating layer is free of repelling, but there is a small amount of repelling. △: There is some repellency in the coating layer, and the percentage of coating layers without repellency is less than 90%. ×: Cracks in the coating layer are present on the entire surface
[0082] 19) Aluminum deposition film adhesion evaluation On the surface layer (B) of the film, aluminum was vapor-deposited to a thickness of 30 nm using a small vacuum vapor deposition device (VWR-400 / ERH, manufactured by ULVAC KIKOU Co., Ltd.). The adhesion state of the aluminum vapor-deposited film was evaluated on the vapor-deposited surface of the obtained vapor-deposited film by a 90° peeling method using 18 mm wide Cellophane Tape (registered trademark) manufactured by Nichiban Co., Ltd. A rating of ◯ was deemed to be acceptable. ○: No peeling of the aluminum vapor deposition film △: The aluminum vapor deposition film is partially peeled off. ×: Aluminum deposition film peeled off over the entire surface.
[0083] (raw resin) Tables 1 to 3 show details of the polypropylene resin raw materials and film formation conditions used in the following Examples and Comparative Examples.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] Example 1 For the base layer (A), a polypropylene homopolymer PP-1 shown in Table 1 was used. For the surface layer (B), 43.2% by weight of polypropylene homopolymer PP-1 shown in Table 1, 52.0% by weight of ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 4.8% by weight of master batch A shown in Table 2 were used. At this time, the melt flow rate (g / 10 min) of the polypropylene resin composition constituting the surface layer (B) was 5.1. For the surface layer (C), a mixture of 93.6% by weight of polypropylene homopolymer PP-1 shown in Table 1 and 6.4% by weight of master batch A shown in Table 2 was used. The base layer (A) was made using a 45 mm extruder, the surface layer (B) was made using a 25 mm extruder, and the surface layer (C) was made using a 20 mm extruder. The raw material resins were melted at 250 ° C. and co-extruded from a T-die into a sheet shape, and the surface layer (B) was cooled and solidified so that it contacted a cooling roll at 30 ° C., and then stretched 4.5 times in the machine direction (MD) at 125 ° C. Next, in a tenter, both ends of the film in the width direction (TD) were clamped with clips, preheated at 168 ° C., stretched 8.2 times in the width direction (TD) at 155 ° C., and heat-set at 165 ° C. while relaxing 6.7% in the width direction (TD). The film formation conditions at this time were film formation conditions a. In this way, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film was corona-treated using a corona treatment machine manufactured by Softal Corona & Plasma GmbH at an applied current value of 0.75 A, and then wound up with a winder. The thickness of the obtained film was 20 μm (thickness of surface layer (B) / base layer (A) / surface layer (C) was 1.3 μm / 17.7 μm / 1.0 μm).
[0088] Example 2 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the amount of resin discharged from the extruder was adjusted so that the thickness of the base layer (A) was 15.1 μm and the thickness of the surface layer (B) was 3.9 μm.
[0089] Example 3 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of a blend of 45.0 wt % polypropylene homopolymer PP-1 shown in Table 1, 52.0 wt % ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 3.0 wt % masterbatch A shown in Table 2.
[0090] Example 4 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of a blend of 1.2 wt % polypropylene homopolymer PP-1 shown in Table 1, 94.0 wt % ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 4.8 wt % master batch A shown in Table 2.
[0091] Example 5 The polypropylene homopolymer PP-1 used in the base layer (A) and surface layer (C) was changed to PP-2 shown in Table 1, and the film formation conditions were changed to b shown in Table 3. Except for this, the same conditions as in Example 1 were used to obtain a 20 μm biaxially oriented polypropylene film.
[0092] Comparative Example 1 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (A) was made of 60.0 wt % polypropylene homopolymer PP-1 and 40.0 wt % PP-4 shown in Table 1, and the surface layer (B) was made of 96.4 wt % polypropylene homopolymer PP-1 and 3.6 wt % masterbatch A shown in Table 2.
[0093] Comparative Example 2 A biaxially oriented polypropylene film of 20 μm was obtained under the same conditions as in Example 1, except that the surface layer (B) was not subjected to the corona treatment.
[0094] Comparative Example 3 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of a blend of 45.0 wt % polypropylene homopolymer PP-1 shown in Table 1, 52.0 wt % ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 3.0 wt % master batch A shown in Table 2, and the surface layer (C) was made of only the polypropylene homopolymer PP-1 shown in Table 1.
[0095] Comparative Example 4 The surface layer (B) was made of a blend of 47.25 wt% polypropylene homopolymer PP-1 shown in Table 1, 52.00 wt% ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 0.75 wt% master batch B shown in Table 2. The surface layer (C) was made of a blend of 98.4 wt% polypropylene homopolymer PP-1 shown in Table 1 and 1.60 wt% master batch B shown in Table 2. The same conditions as in Example 1 were used except that the surface layer (C) was formed so that it was in contact with the cooling roll, and a 20 μm biaxially oriented polypropylene film was obtained.
[0096] Comparative Example 5 A biaxially oriented polypropylene film of 20 μm was obtained under the same conditions as in Example 1, except that the base layer (A) was made of 99.0 wt% polypropylene homopolymer PP-1 shown in Table 1 and 1.0 wt% stearyl diethanolamine stearate (KYM-4K, Matsumoto Oil Co., Ltd.) as an antistatic agent.
[0097] Comparative Example 6 The film formation conditions were the same as in Example 1, except that they were changed to c in Table 3, to obtain a 20 μm biaxially oriented polypropylene film.
[0098] The raw materials, production methods, and physical properties of the films used in the above Examples and Comparative Examples are shown in Tables 4 and 5.
[0099] [Table 4]
[0100] [Table 5]
[0101] The biaxially oriented polypropylene films obtained in Examples 1 to 5 had high lamination strength, no peeling of the aluminum deposition, no repelling of the coating liquid, and excellent adhesion. In addition, the roll had no wrinkles and was excellent in blocking resistance. In contrast, the films of Comparative Examples 1 to 6 were all poor in adhesion and roll winding condition. [Industrial Applicability]
[0102] The biaxially oriented polypropylene film of the present invention exhibits excellent adhesion in deposition, coating, and lamination with other films, and has good slip properties and blocking resistance, making it suitable for processing raw rolls. It can also be used for food packaging and labels used for confectionery, etc., and is industrially useful because the film can be produced at low cost.
Claims
1. A biaxially oriented polypropylene film having a base layer (A) made of a polypropylene resin composition containing a polypropylene homopolymer and / or a polypropylene resin copolymerized with an α-olefin having 4 or more carbon atoms, a surface layer (B) made of a polypropylene resin composition containing a polypropylene homopolymer and / or a polypropylene resin copolymerized with an α-olefin having 4 or more carbon atoms on one side of the base layer (A), and a surface layer (C) made of a polypropylene homopolymer and / or a polypropylene resin copolymerized with an α-olefin having 4 or more carbon atoms on the opposite side of the base layer (B) of the surface layer (A), the surface layer (B) satisfying the following (1) to (5) and (8), and the surface layer (C) satisfying the following (6), (7) and (9): (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 nm or more and 5.5 nm or less. (4) Martens hardness of 248 N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 μm or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness of 270 N / mm 2 That's all. (8) The polypropylene resin composition constituting the surface layer (B) contains an antiblocking agent. (9) The polypropylene resin composition constituting the surface layer (C) contains an antiblocking agent.
2. The biaxially oriented polypropylene film according to claim 1, wherein the surface layers (B) of the biaxially oriented polypropylene film have a dynamic friction coefficient of 0.6 or less at 23°C.
3. 3. The biaxially oriented polypropylene film according to claim 1, wherein the haze value of the biaxially oriented polypropylene film is 5% or less.
4. The biaxially oriented polypropylene film according to any one of claims 1 to 3, wherein the surface layer (B) has a maximum peak height Rp + maximum valley depth Rv of 30 nm or more and 50 nm or less.
5. The biaxially oriented polypropylene film according to any one of claims 1 to 4, wherein the air release time of the biaxially oriented polypropylene film is 10 seconds or less.
6. The biaxially oriented polypropylene film according to any one of claims 1 to 5, wherein the thickness of the biaxially oriented polypropylene film is 9 μm or more and 200 μm or less.
7. A laminate of the biaxially oriented polypropylene film according to any one of claims 1 to 6 and a non-oriented polyethylene film.
8. The laminate according to claim 7, having a laminate strength of 2.0 N / 15 mm or more.
Citation Information
Patent Citations
Biaxially oriented polypropylene film
WO2007094072A1
Biaxially stretched laminated polypropylene film
WO2017169952A1
Biaxially oriented polypropylene film
WO2017170244A1
Biaxially oriented polypropylene-based film
WO2018142983A1